Bioinformatics Analysis of the Mechanisms of Diabetic Nephropathy via Novel Biomarkers and Competing Endogenous RNA Network - Guo, Mingfei; Dai, Yaji; Jiang, Lei; Gao, Jiarong (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) is one of the common chronic complications of diabetes with unclear molecular mechanisms, which related to end-stage renal disease (ESRD) and chronic kidney disease (CKD). Our study intended to constructe ceRNA network via bioinformatics analysis to determine the potential molecular mechanisms of DN pathogenesis. The microarray dataset (GSE30122, GSE30529) were downloaded from the Gene Expression Omnibus database to find differentially expressed genes (DEGs). GSE51674 and GSE155188 dataset were used to identified the differentially expressed miRNAs and lncRNAs, respectively. The DEGs between normal and DN renal tissues were performed using Linear Models for Microarray (LIMMA) package. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were carried out to reveal the mechanisms of DEGs in the progression of DN. The protein-protein interactions (PPI) of DEGs were performed by STRING database. The lncRNA-miRNA-mRNA ceRNA network was constracted and visualized via Cytoscape on the basis of the interaction generated through the miRDB and TargetScan databases. A total of 94 significantly up-regulated and 14 down-regulated mRNAs, 31 up-regulated and 121 down-regulated miRNAs, 9 up-regulated and 81 down-regulated lncRNAs were identified. GO and KEGG pathways enriched in several functions and expression pathways, such as inflammatory response, immune response, identical protein binding, NF-kappa B signaling pathway, and PI3K-Akt signaling pathway. Based on the analysis of the ceRNA network, 5 DElncRNA (SNHG6, KCNMB2-AS1, LINC00520, DANCR, and PCAT6), 5 DEmiRNAs (miR-130b-5p, miR-326, miR-374a-3p, miR-577, and miR-944), and 5 DEmRNAs (PTPRC, CD53, IRF8, IL10RA, and LAPTM5) were demonstrated to be related to the pathogenesis of DN. Our research identified key genes related to potential mechanism of DN and provided new lncRNA-miRNA-mRNA ceRNA network contributed to diagnostic and potential therapeutic targets for DN.